KESIAPAN PETUGAS/KARYAWAN RUMAH SAKIT UMUM dr. ZAINOEL ABIDIN DALAM PENANGGULANGAN BENCANA KEBAKARAN GEDUNG - Muliadi .; Mulyadi .; Endang Meutiawati (Jurnal Ilmu Kebencanaan : Program Pascasarjana Unsyiah, 2017)
Hospitals as one of the health care facilities are part of the health resources that are needed in supporting the implementation of health efforts. The provision of health services in hospitals has very complex characteristics and organization. The danger of fire risk in the hospital building is sourced from several activities or equipment that exist in the hospital itself, such as the use of large-capacity electric appliances (radiology room), this study aims to Detect facilities of fire protection equipment in supporting fire disaster prevention at General Hospital The area of dr. Zainoel Abidin Banda Aceh and know the readiness of officers / employees of the Regional General Hospital dr. Zainoel Abidin Banda Aceh in the face of fire disaster. This type of research is a descriptive qualitative research type with data acquisition through observation, interview, observation and direct examination. Dr Zainoel Abidin General Hospital is a Class A Type Hospital in Education with Basic Decision of Minister of Health RI Number: 1062 / MENKES / SK / 2011 dated February 22, 2009. With a bed capacity of 740 beds. With 40 buildings in two locations. Fire safety hazard in dr. Zainoel Abidin Banda Aceh has been very good. This is obtained from the results of the audit as follows: Completeness of the site with the value of condition 9.00 of total weight Reliability of Building Safety System (KSKB) of 26%. Rescue facilities with a condition value of 6.57 of the total Reliability of Building Security System (KSKB) of 25%. Elements were found in the absence of helicopter field facilities. Passive protection system with value of condition 7,704 from total of Reliability of Building Safety System (KSKB) equal to 26%. Passive protection system is good. An active protection system with a condition value of 5,342 of the total reliability of the Building Safety System (KSKB) of 24%, the element that has not functioned optimally is the extinguishing system, sprinkler and operational control room. Keywords: fire hospital building, personnel preparedness, fire danger security